Important characteristics of an entrepreneur in relation to risk taking: Czech Republic case study - Ludmila Kozubíková; Ján Dvorský; Martin Cepel; Adam P. Balcerzak (Journal of International Studies)
New businesses arising at the market usually operate in the sector of small and medium-sized enterprises and account for a significant part of the whole global economy. Not only the success of a start-up company, but also its sequel within the SME sector are significantly influenced by entrepreneur's personality. The aim of this article is to explore the attitude to financial risk in relation to sociodemographic characteristics (gender, education, age) and the most important personality traits of entrepreneurs (risk-taking, decisiveness, optimism). We have analyzed the data collected from 1141 respondents during 2015 in 14 regions of Czech Republic. Empirical results of our paper show that the researched entrepreneurs rather can't manage financial risks in their firms regardless their gender, education, age or personality traits. Most entrepreneurs consider the importance of financial risk to increase during the crisis period. These opinions differed in relation to age, gender and such personality traits as "decisiveness" and "optimism". The results also show that the entrepreneurs try to minimise the financial risk through building-up reserves in relation to such qualities as "risk-taking" and "decisiveness" in comparison to a rather negative attitude to "optimism".